Determinan IMT Orang Dewasa di Indonesia: Pendekatan Analisis Multilevel - Kismaningrum, Dhea Riana (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2018)
Determinants of Body Mass Index among Indonesian Adults: a multilevel analysis. Obesity is caused by an imbalance of incoming calories and outgoing energy measured by body mass index (BMI). The emergence of this imbalance is the role of various determinants. The aim of this study was to identify compositional and contextual determinants of BMI among Indonesian adults in 16 provinces above the national obesity prevalence average. The study used a cross-sectional design with the number of respondents 180.352 adults aged 19-44 years in Indonesia. Compositional determinant data obtained from National Basic Health Research in 2013. Contextual determinant data obtained from Village Potential Statistics in 2011, Statistics of Environmental Care Behavior in 2013 and Statistics on Food-Non-Food Consumption Expenditures and Household Income/Revenue in 2013. The study used multilevel linear regression analysis. Compositional determinants that have a dominant relationship with BMI is economic status. Contextual determinants that have a dominant relationship with BMI are increased access to motorized vehicle use and consumption of fast food in line with increasing BMI. Policies that support increased access to healthy food and physical activity through the facility available around living quarters and balanced lifestyle education are expected to reduce risk of non-communicable diseases related to BMI in the community